An Efficient Method for Solving System of Third-Order Nonlinear Boundary Value Problems. (2nd June 2011) - Noor, Muhammad; Noor, Khalida; Waheed, Asif; Al-Said, Eisa A.
Abstract : we use the modified variation of parameters method for finding the analytical solution of a system of third-order nonlinear boundary value problems associated with obstacle, unilateral, and contact problems. The results are calculated in terms of convergent series with easily computable components. The suggested technique is applied without any discretization, perturbation, transformation, and restrictive assumptions. Moreover, it is free from round off errors. Some examples are given to illustrate the implementation and efficiency of the modified variation of parameters method.